HOME CHRONOTOPE IN MODERN UKRAINIAN LITERARY FAIRYTALES (ON THE BASE OF VALERIY SHEVCHUK’S «THE LADY OF FLOWERS») - Дибовська, О. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the problem of chronotope of home in fairytales. The researches of Ukrainian and foreign scientists are analyzed. The models of chronotope of the home according to the specific features of literary fairytales are defined. The presence of the home-chronotope in modern Ukrainian literary fairytales on the base of Valeriy Shevchuk’s «The lady of flowers» is analyzed, too.